2021
DOI: 10.1152/jn.00497.2020
|View full text |Cite
|
Sign up to set email alerts
|

The retrotrapezoid nucleus and the neuromodulation of breathing

Abstract: Breathing is regulated by a host of arousal and sleep-wake state-dependent neuromodulators in order to maintain respiratory homeostasis. Modulators such as acetylcholine, norepinephrine, histamine, serotonin (5-HT), adenosine triphosphate (ATP), substance P, somatostatin, bombesin, orexin, and leptin can serve complementary or off-setting functions depending on the target cell type and signalling mechanisms engaged. Abnormalities in any of these modulatory mechanisms can destabilize breathing, suggesting modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 345 publications
3
9
0
1
Order By: Relevance
“…Furthermore, the significant association observed in the present study between the PAGsm and SNpc hypoplasia previously detected (Lavezzi et al, 2020) (15 of the 17 cases with hypoplasia of the PAGsm, in fact, also presented SNpc hypoplasia) leads us to believe that the two mesencephalic structures are connected to each other and joined through synaptic descending ways to lower brainstem nuclei of the respiratory network. This view finds support in the experimental study by Lima et al on animal models (Lima et al, 2018), showing evidence of direct projection from SNpc to PAG and, from here, to the medullary retrotrapezoid nucleus, a group of glutamatergic neurons expressing the transcription factor PHOX2B and involved in activation of breathing (Moreira et al, 2021;Takakura et al, 2014). Interconnections between the PAG and other respiratory nuclei of the medulla oblongata (as retroambiguus and tractus solitarius nuclei) have also been reported in further studies on rats (Huang et al, 2000;Klop et al, 2002;Subramanian, 2013;Subramanian & Holstege, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the significant association observed in the present study between the PAGsm and SNpc hypoplasia previously detected (Lavezzi et al, 2020) (15 of the 17 cases with hypoplasia of the PAGsm, in fact, also presented SNpc hypoplasia) leads us to believe that the two mesencephalic structures are connected to each other and joined through synaptic descending ways to lower brainstem nuclei of the respiratory network. This view finds support in the experimental study by Lima et al on animal models (Lima et al, 2018), showing evidence of direct projection from SNpc to PAG and, from here, to the medullary retrotrapezoid nucleus, a group of glutamatergic neurons expressing the transcription factor PHOX2B and involved in activation of breathing (Moreira et al, 2021;Takakura et al, 2014). Interconnections between the PAG and other respiratory nuclei of the medulla oblongata (as retroambiguus and tractus solitarius nuclei) have also been reported in further studies on rats (Huang et al, 2000;Klop et al, 2002;Subramanian, 2013;Subramanian & Holstege, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…However, as the VAs supply the brainstem structures containing ventilatory control centres and central chemoreceptors, one could reasonably anticipate that the brain may protect those areas with high priority, represented by a superior CVR in the posterior than anterior arteries. While this remains teleological speculation, there is recent murine in vitro and in vivo evidence suggesting that, rather than the vasodilatation typically seen in the cerebral vascular tree during hypercapnia, the vessels surrounding the retrotrapezoid nucleus (RTN) – a critical group of central chemoreceptor neurons (Guyenet et al., 2018, 2019; Moreira et al., 2021) – may even constrict in response to elevated PnormalaCO2 (Cleary et al., 2020; Hawkins et al., 2017). These studies demonstrated that reductions in pH‐mediated ATP release and purinergic signalling resulting in maintenance of vascular tone and even vasoconstriction.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…asynchronous) to the respiratory pattern generator. 9 It has been proposed that in pathophysiological contexts characterized by breathing disorders (e.g., CHF), alterations in RTN-mediated chemoreflex function induces instability in the respiratory control network, fostering a feed-forward mechanism that perpetuates breathing irregularity. 8 , 57 It is worth noting that no specific cellular or molecular mechanisms have been identified as putative pathways involved in RTN chemoreceptor-mediated disordered breathing.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 , 7 The molecular identity of the sensors that mediate central respiratory chemoreception has been extensively studied in the retrotrapezoid nucleus (RTN) since it is considered a major nodal point for regulation of respiration during variations in brain PCO 2 . 8 , 9 Indeed, the 2-pore domain K + background channel TASK-2 and the G-coupled proton sensor GPR4 has both been implicated in H + sensing in RTN chemoreceptor neurons. 10 Despite the intrinsic chemo-sensitive properties of RTN neurons, recent evidence supports the role of glial cells on the regulation of breathing.…”
Section: Introductionmentioning
confidence: 99%